Penerapan Metode Design Thinking untuk Perancangan UI/UX Website MARQETIQ - Anansyah Wira Diharja; Riyan Abdul Aziz; Muhammad Setiyawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In the rapidly evolving digital era, the digital marketing service industry in Indonesia faces the challenge of providing more effective and relevant solutions amid intense competition. This research utilizes the Design Thinking methodology to develop the UI/UX of the MARQETIQ website, aiming to enhance user experience by offering digital marketing services tailored to clients' specific needs. Through the five stages of Design Thinking: Empathize, Define, Ideate, Prototype, and Test. The researchers gained deep insights into user needs, formulated key problems, and created and tested innovative design solutions. The research findings indicate that this approach successfully resulted in a more intuitive and responsive website, facilitated the ordering process, and improved client satisfaction and loyalty. These findings demonstrate that applying the Design Thinking approach can significantly enhance user experience and the relevance of services in a digital marketing platform..